2012
DOI: 10.1038/nmeth.1897
|View full text |Cite
|
Sign up to set email alerts
|

Rapid optical control of nociception with an ion-channel photoswitch

Abstract: Local anesthetics are effective in suppressing pain sensation, but most of these compounds act non-selectively, inhibiting the activity of all neurons. Moreover, their actions abate slowly, preventing precise spatial and temporal control of nociception. We have developed a photoisomerizable molecule named QAQ (Quaternary ammonium – Azobenzene – Quaternary ammonium) that enables rapid and selective optical control of nociception. QAQ is membrane-impermeant and it has no effect on most cells, but it infiltrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
210
0
12

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(223 citation statements)
references
References 29 publications
1
210
0
12
Order By: Relevance
“…These experiments were motivated by the concept of using TRPV1 channels as portals for delivering charged drug molecules into primary pain-sensing neurons to inhibit pain signaling in vivo selectively Kim et al 2010;Liu et al 2011;Roberson et al 2011), an approach recently extended to using light-controlled QX-314 derivatives (Mourot et al 2012) and to using TRPA1 channels as portals (Lennertz et al 2012). Our finding that QX-314 can enter through the standard pore and does not require pore dilation is likely advantageous for in vivo and potential clinical use because pore dilation typically requires large concentrations of agonist (Banke et al 2010;Chung et al 2008), which may be difficult to deliver and maintain in vivo (e.g., using perineural infusion to produce nerve block).…”
Section: Discussionmentioning
confidence: 99%
“…These experiments were motivated by the concept of using TRPV1 channels as portals for delivering charged drug molecules into primary pain-sensing neurons to inhibit pain signaling in vivo selectively Kim et al 2010;Liu et al 2011;Roberson et al 2011), an approach recently extended to using light-controlled QX-314 derivatives (Mourot et al 2012) and to using TRPA1 channels as portals (Lennertz et al 2012). Our finding that QX-314 can enter through the standard pore and does not require pore dilation is likely advantageous for in vivo and potential clinical use because pore dilation typically requires large concentrations of agonist (Banke et al 2010;Chung et al 2008), which may be difficult to deliver and maintain in vivo (e.g., using perineural infusion to produce nerve block).…”
Section: Discussionmentioning
confidence: 99%
“…Quaternary ammonium-azobenzene-quaternary ammonium (QAQ) is a photo-switchable compound developed on the basis of lidocaine and its derivative QX-314, local anesthetics that block voltage-gated channels [7,8]. Trans-QAQ is capable of blocking ion channels, but the cis form is inactive.…”
Section: Photo-compounds For Voltage-gated Channelsmentioning
confidence: 99%
“…Under prolonged pain conditions, QAQ inhibitory effect does not seem to need a co-targeting of TRPV1, due to the fact that active nociceptive neurons would allow its internalization [7,8]. An in vivo test was also performed by topical application of QAQ to rats' cornea, where von Frey hair evoked responses demonstrated that trans-QAQ could block blink sensitivity f ollowing irradiation of 380 nm light [8].…”
Section: "Photo-pharmacologicalmentioning
confidence: 99%
“…This approach involves genetic manipulation of the protein so that a reactive cysteine residue can be placed in a specific site on the receptor. A second method involves a small molecule ligand that contains a head group that resembles a known receptor agonist or antagonist [74,[79][80][81][82][83][84][85]. The affinity is light dependent, the conformation of one isomer interferes with binding and/or activation and the other permits it.…”
Section: Photoswitchable Ion Channels and Receptorsmentioning
confidence: 99%